P37 Effectiveness of an ultrasound clinic (USC) in managing long-acting reversible contraception (LARC) related problems within an integrated sexual health (ISH) clinic. (16th June 2022) - Dickinson, Molly; Forbes, Kimberley; Cooney, Grainne; Day, Sara
Abstract : Introduction: LARC uptake, including intrauterine contraception (IUC), has increased over the last decade. The referral rate to our regional complex LARC clinic is high and demand continues to increase. An in-house pelvic USC was established to support/triage complex LARC clinic referrals and train ISH staff to perform pelvic ultrasound. Methods: Electronic records were reviewed of USC referrals received between September and December 2021. Results: Of 58 referrals, 57 were female (one trans-male). 58.6%(34/58) aged <30yrs. 72.4%(42/58) were nulliparous. 14.5%(8/58) were post-partum, with 75%(6/8) breastfeeding. Referral indications were: check IUC position 41.4%(24/58), IUC-related pain 31.0%(18/58), abnormal bleeding 19.0%(11/58), history necessitating ultrasound pre-fit eg fibroids or pain 8.6%(5/58). 50 individuals attended the USC and 48 were scanned (2 already scanned elsewhere). Of 46/48 that had IUC in situ, the device was correctly positioned (+/- other pathology) in 69.6%(32/46) and a malposition or IUC complication was identified in 30.4%(14/46): perforation n=1, embedment n=3, low lying n=5, septate uterus n=1, embedded in caesarean scar n=1, significant fibroids n=2, rotated n=1. Outcomes following ultrasound were - 5/48(10.4%) gynaecology referral - 5/48(10.4%) complex LARC referral - 2/48(4.2%) gynaecology and complex LARC referral - 34/48(70.8%) managed within the USC/sexual health/general contraception clinic - 1/48(2.1%) referred for 3D imaging - 1/48(2.1%) GP referral The USC averted 85.4%(41/48) complex LARC appointments. Two staff members received US training. Discussion: The USC supported our ISH by directing complex LARC referrals to the most appropriate service, reducing waiting time and increasing capacity for procedural intervention in the complex LARC clinic and developing staff scanning skills.